Pentastira eminei sp. nov. (Hemiptera, Fulgoromorpha, Cixiidae) from Türkiye, and notes on other Pentastira spp. in Türkiye and the Middle East - Demi̇rel Ersi̇n; Erbey, Mahmut (Zootaxa, 2022)
Pentastira eminei sp. nov. (Hemiptera, Auchenorrhyncha, Fulgoromorpha, Cixiidae) from Central Anatolia, Türkiye is described and the status of the genus in Türkiye reevaluated. Pentastira superans Logvinenko, 1976 in Türkiye, as reported in earlier faunistic studies, is doubtful and its removal from the Cixiidae species of Türkiye is recommended. An identification key and a brief evaluation of the species of the genus Pentastira Kirschbaum, 1868 in Türkiye and the Middle East is included.